Development of Mobile Application for Accounting Subject - Hakim Azammullah, Muhammad Akmal; Ahmad Zaki, Nadia Akma; Manaf, Abdi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study aims to develop a mobile application called